2018
DOI: 10.1111/cogs.12692
|View full text |Cite
|
Sign up to set email alerts
|

Statistical Learning Is Not Age‐Invariant During Childhood: Performance Improves With Age Across Modality

Abstract: Humans are capable of extracting recurring patterns from their environment via statistical learning (SL), an ability thought to play an important role in language learning and learning more generally. While much work has examined statistical learning in infants and adults, less work has looked at the developmental trajectory of SL during childhood to see whether it is fully developed in infancy or improves with age, like many other cognitive abilities. A recent study showed modality‐based differences in the ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
52
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(63 citation statements)
references
References 48 publications
5
52
1
1
Order By: Relevance
“…The pattern of correlations was stable across sessions, another indication of task stability: The two auditory tasks were not correlated, whereas visual task and the nonlinguistic auditory task were. This pattern of correlation may seem counterintuitive because the tasks do not group together on the basis of modality; however, it is compatible with a set of recent findings suggesting that tasks using linguistic stimuli (like syllables) behave differently from tasks using nonlinguistic stimuli, regardless of modality (Siegelman et al, 2018a;Shufaniya & Arnon, 2018). An additional stable pattern was the positive correlation between the SL tasks and working memory, a pattern that has been reported in some adult studies (Misyak & Christiansen, 2012) but not others .…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…The pattern of correlations was stable across sessions, another indication of task stability: The two auditory tasks were not correlated, whereas visual task and the nonlinguistic auditory task were. This pattern of correlation may seem counterintuitive because the tasks do not group together on the basis of modality; however, it is compatible with a set of recent findings suggesting that tasks using linguistic stimuli (like syllables) behave differently from tasks using nonlinguistic stimuli, regardless of modality (Siegelman et al, 2018a;Shufaniya & Arnon, 2018). An additional stable pattern was the positive correlation between the SL tasks and working memory, a pattern that has been reported in some adult studies (Misyak & Christiansen, 2012) but not others .…”
Section: Resultssupporting
confidence: 85%
“…SL tasks using linguistic stimuli (syllables) are more affected than visual tasks by the exact stimuli used and show evidence of L1 influences (Siegelman et al, 2018b). Developmentally, the effect of age on performance seems different for tasks using linguistic stimuli: Whereas performance on visual and nonlinguistic auditory SL improves during childhood (ages 5-12 years), performance on linguistic auditory SL does not (Shufaniya & Arnon, 2018). Since studies finding modalitybased differences often use linguistic auditory tasks (Emberson et al, 2011;, previously reported differences (and similarities) may be driven not only by modality by also by the specific stimuli use.…”
Section: Discussionmentioning
confidence: 93%
“…For example, while it is well documented that humans are sensitive both to the transitional statistics and to the aggregated frequency and variance of exemplars in the input, Thiessen, Kronstein, and Hufnagle () claimed that from a computational perspective, the assimilation of these two types of regularities is likely subserved by different processes. Concurring behavioral evidence also showed patterns of informational‐specificity (specifically, in learning adjacent vs. non‐adjacent contingencies: e.g., Newport & Aslin, , and verbal vs. nonverbal material: Shufaniya & Arnon, ; Siegelman, Bogaerts, Elazar, Arciuli, & Frost, ). Lastly, joining these group‐level observations are preliminary individual‐differences studies revealing patterns of modality and informational‐specificity in SL.…”
Section: Linking Sl and Language: Moving Beyond The Proof Of Concept mentioning
confidence: 99%
“…The development of online measures is especially important for studies investigating SL in early-school-aged children due to the fact that the traditional 2-AFC questions require explicit decision-making, a skill that young children have difficulties with (Bialystok, 1986). Children’s performance on 2-AFC questions in VSL tasks is known to increase between the ages of 5 and 12 years (Arciuli and Simpson, 2011; Raviv and Arnon, 2017; Shufaniya and Arnon, 2018). For this reason, solely using 2-AFC questions to assess early-school-aged children’s performance may not provide a complete picture of their SL abilities.…”
Section: Introductionmentioning
confidence: 99%